2000
DOI: 10.1080/080352500750027574
|View full text |Cite
|
Sign up to set email alerts
|

Selected trace elements and minerals in cord blood: association with lipids and lipoproteins at birth

Abstract: Recent studies have found that some minerals are associated with lipoprotein metabolism, peroxidation and coronary heart disease. The present study was designed to obtain information on the relationship between the concentrations of minerals and trace elements and those of lipids, lipoproteins and apolipoproteins (Apo) in cord blood. Seventy-nine healthy singleton normoweight full-term newborns without foetal distress according to Apgar scores were studied. The quartile distribution of neonates, according to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 28 publications
2
11
0
Order By: Relevance
“…This is consistent with a study conducted among Spanish newborns 24 and a cross-sectional study among hyperlipidemic Iraqi men, 20 although there was no correlation between copper and triglycerides among controls in the Iraqi study. Several other studies in children or adults have found positive relationships between copper and several forms of cholesterol, 19 HDL cholesterol, 15 or an unfavorable lipid profile (LDL/HDL >2.2).…”
Section: Discussionsupporting
confidence: 91%
“…This is consistent with a study conducted among Spanish newborns 24 and a cross-sectional study among hyperlipidemic Iraqi men, 20 although there was no correlation between copper and triglycerides among controls in the Iraqi study. Several other studies in children or adults have found positive relationships between copper and several forms of cholesterol, 19 HDL cholesterol, 15 or an unfavorable lipid profile (LDL/HDL >2.2).…”
Section: Discussionsupporting
confidence: 91%
“…440relationship between Cu and lipids found in previous studies. Thus, a positive association 441 between Cu and triglycerides has been observed in umbilical cord serum(Bastida et al, 2000; 442Wells et al, 2014) and between Cu and cholesterol in adults(Ghayour-Mobarhan et al, 2005).443 Nulliparous women those with an age between 25 and 29 years and those belonging to the lowest social class had the highest Cu concentrations. The relationship between maternal age 445 and some indicator of economic status (such as income or automobile possession) and cord 446 blood Cu concentrations was examined by Parajuli et al (2012); however they did not obtain 447 any statistically significant result (Parajuli et al, 2012).…”
mentioning
confidence: 98%
“…Klevay (1975) formulated the hypothesis that diets with high zinc/copper ratios are hypercholesterolemics. Our group (Bastida et al , 2000) found that in cord-blood calcium, magnesium, iron, zinc and copper levels were correlated with lipid and lipoproteins concentrations. Moreover, the inclusion of chromium decreases cholesterolemia and improves insulin sensitivity (Albarracin et al , 2007).…”
Section: Mineralsmentioning
confidence: 91%
“…This hypothesis was corroborated in newborn infants as high serum cholesterol levels were correlated to high serum zinc/copper ratios (Bastida et al , 2000). The levels of neonatal HDLc were also related to serum iron values (Bastida et al , 2000). Data from our group (Bocanegra et al , 2003; indicate that the zinc/copper dietary intake ratio, net iron absorption, and plasma cholesterol levels were lower in the Nori-fed rats than in the Konbu-fed ones, suggesting that this mineral ratio and iron bioavailability may infl uence cholesterolemia (Fig.…”
Section: Mineralsmentioning
confidence: 94%